Application of the Stockwell Transform to Electroencephalographic Signal Analysis during Gait Cycle - Ortiz, Mario; Rodríguez-Ugarte, Marisol; Iáñez, Eduardo; Azorín, José M. (Frontiers in Neuroscience, 2017)
The analysis of electroencephalographic signals in frequency is not usually performed by transforms that can extract the instantaneous characteristics of the signal. However, the non-steady state nature of these low voltage electrical signals makes them suitable for this kind of analysis. In the paper a novel tool based on Stockwell transform is tested, and compared with techniques as Hilbert-Huang transform and Fast Fourier Transform, for several healthy individuals and patients that suffer from low limb disability. Methods are compared with the Weighted Discriminator, a recent developed comparison index. The tool developed can improve the rehabilitation process associated to lower limb exoskeletons with the help of a Brain-Machine Interface.